Desferrioxamine Reduces Oxidative Stress in the Lung Contusion - Basaran, Umit Nusret; Ayvaz, Suleyman; Aksu, Burhan; Karaca, Turan; Cemek, Mustafa; Karaboga, Ihsan; Inan, Mustafa; Aksu, Feyza; Pul, Mehmet (HINDAWI LTD, 2013)
Our hypothesis in this study is that desferrioxamine (DFX) has therapeutic effects on experimental lung contusions in rats. The rats were divided into four groups (n = 8): control, control+DFX, contusion, and contusion+DFX. In the control+DFX and contusion+DFX groups, 100 mg/kg DFX was given intraperitoneally once a day just after the contusion and the day after the contusion. Contusions led to a meaningful rise in the malondialdehyde (MDA) level in lung tissue. MDA levels in the contusion+DFX group experienced a significant decline. Glutathione levels were significantly lower in the contusion group than in the control group and significantly higher in the contusion+DFX group. Glutathione peroxidase (GPx) and superoxide dismutase (SOD) levels in the contusion group were significantly lower than those in the control group. In the contusion+DFX group, SOD and GPx levels were significantly higher than those in the contusion group. In light microscopic evaluation, the contusion and contusion+DFX groups showed edema, hemorrhage, alveolar destruction, and leukocyte infiltration. However, histological scoring of the contusion+DFX group was significantly more positive than that of the contusion group. The iNOS staining in the contusion group was significantly more intensive than that in all other groups. DFX reduced iNOS staining significantly in comparison to the contusion group. This study showed that DFX reduced oxidative stress in lung contusions in rats and histopathologically ensured the recovery of the lung tissue.
Keywords: BLUNT CHEST TRAUMA; PULMONARY CONTUSION; NITRIC-OXIDE; SUPEROXIDE-DISMUTASE; HIF-1-ALPHA ACCUMULATION; LIPID-PEROXIDATION; HYDROXYL RADICALS; FENTON REACTION; INJURY; GLUTATHIONE; Science & Technology - Other Topics